The level of interplay required between expatriates and locals in a MNC's subsidiary to effectively transfer knowledge in order to gain strategic competitive advantage - Rowley, Colin (University of Pretoria, 2017)
Mini Dissertation (MBA)--University of Pretoria, 2017.